2009
DOI: 10.1021/jf901656k
|View full text |Cite
|
Sign up to set email alerts
|

Iron Is an Essential Cause of Fishy Aftertaste Formation in Wine and Seafood Pairing

Abstract: Fishy aftertaste is sometimes perceived in wine with fish and seafood pairing. However, what component of wine clashes with seafood or what compound contributes to the unpleasant fishy aftertaste in the mouth remains an open problem. First, intensities of unpleasant fishy aftertaste of wine and dried scallop pairings were rated by sensory analysis. Second, components of the wines were analyzed. Strong positive correlations were found between the intensity of fishy aftertaste and the concentration of both total… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 15 publications
(16 reference statements)
1
27
0
Order By: Relevance
“…In the presence of Fe 3+ , the spirolactam ring was opened and a highly delocalized π-conjugated structure formed with a sharp Fe 3+ -selective fluorescence enhancement response. 5 Under the optimum conditions, the fluorescence intensity enhancement is linear to Fe 3+ concentration from 6.0×10 -8 to 7.2×10 -6 M with a detection limit of 1.4×10 -8 M. The present method was effectively applied to Fe 3+ detection in tap water and industrial waste water with a recovery among 94~106%. 10 Fluorescence enhance mechanism is presumably due to the chelation of Fe 3+ with the oxygen atoms of the amide groups, which results in the formation of the open-ring form and so the enhancement of fluorescence signals accordingly (Fig.…”
Section: Organic Fluorescent Sensing Materialsmentioning
confidence: 78%
See 1 more Smart Citation
“…In the presence of Fe 3+ , the spirolactam ring was opened and a highly delocalized π-conjugated structure formed with a sharp Fe 3+ -selective fluorescence enhancement response. 5 Under the optimum conditions, the fluorescence intensity enhancement is linear to Fe 3+ concentration from 6.0×10 -8 to 7.2×10 -6 M with a detection limit of 1.4×10 -8 M. The present method was effectively applied to Fe 3+ detection in tap water and industrial waste water with a recovery among 94~106%. 10 Fluorescence enhance mechanism is presumably due to the chelation of Fe 3+ with the oxygen atoms of the amide groups, which results in the formation of the open-ring form and so the enhancement of fluorescence signals accordingly (Fig.…”
Section: Organic Fluorescent Sensing Materialsmentioning
confidence: 78%
“…At pH 5.5, the sensing system displayed an excellent calibration curve over a wide Fe 3+ 105 concentration range from 6.0×10 −4 to 1.0×10 −7 M with a low detection limit of 5.0×10 −8 M. When it was applied to directly determinate Fe 3+ in different real samples, such as straw of rice, spinach and various water samples, All the RSDs got were less than 2.0%. Importantly, the sensor was reversible and could be 5 easily regenerated from high concentration to low concentration. Owing to its good response characteristics, high stability, well reproducibility, wide calibration range, low detection limit and excellent selectivity, the proposed sensor could be ranked among the best Fe 3+ fluorescent sensors reported so far.…”
Section: Polymer-based Fluorescent Sensing Materialsmentioning
confidence: 99%
“…Reports of a ferrous taste, an unpleasant fishy and/or metallic odour, and possibly also bitterness in the mouth are not uncommon [20]. Intriguingly, the latest research has identified that it is the ferrous ion in some red wines that gives rise to the unpleasant fishy aftertaste [21].…”
Section: Some Classic Combinations To Avoid Red Wine and Seafoodmentioning
confidence: 99%
“…Other combinations that have been recommended, so far on the basis of personal opinion rather than any obvious evidential footing, include sherry and dry white wine with kippers and mackerel [20,24]. Note here that highly acidic wines have iron chelating properties, while both fino and manzanilla sherries have a relatively low ferrous ion concentration [21]. Orange juice after toothpaste Many of us have had the unpleasant experience of drinking orange juice that tastes exceedingly bitter, not sweet, after having just brushed our teeth (e.g.…”
Section: Some Classic Combinations To Avoid Red Wine and Seafoodmentioning
confidence: 99%
“…Thus far, the studies have demonstrated that most interactions result in a mutual suppression in the fl avor intensities of both elements, not an enhancement (Nygren et al , 2002;Madrigal-Galan and Heymann (2006). Examples are a reduction in the bitter/astringent sensations of red wines, by the reaction between wine tannins and food proteins (see Haslam et al , 1992); the action of food gums, gels and oils in coating taste receptors, making them less responsive to gustatory sensations (Kinsella, 1990;Hollowood et al , 2002); infl uences of food chemicals and dilution in the mouth on the volatility of wine aromatics (Hodgson et al , 2005;Bayarri et al , 2007); and the action of metal ions in wine in promoting fatty acid oxidation (Tamura et al , 2009).…”
Section: Future Trendsmentioning
confidence: 99%